Use of patient‐reported outcomes in heart failure: from clinical trials to routine practice. (30th January 2023) - Savarese, Gianluigi; Lindenfeld, Joann; Stolfo, Davide; Adams, Kirkwood; Ahmad, Tariq; Desai, Nihar R.; Ammirati, Enrico; Gottlieb, Stephen S.; Psotka, Mitchell A.; Rosano, Giuseppe M.C.; Allen, Larry A.
Abstract: Heart failure (HF) is a complex syndrome that affects mortality/morbidity and acts at different levels in the patient's life, resulting in a drastic impairment in multiple aspects of daily activities (e.g. physical, mental/emotional, and social) and leading to a reduction in quality of life. The definition of disease status and symptom severity has been traditionally based on the physician assessment, while the patient's experience of disease has been long overlooked. The active participation of patients in their own care is necessary to better understand the perception of disease and the multiple aspects of life affected, and to improve adherence to treatments. Patient‐reported outcomes (PROs) aim to switch traditional care to a more patient‐centred approach. Although PROs demonstrated precision in the evaluation of disease status and have a good association with prognosis in several randomized controlled trials, their implementation into clinical practice is limited. This review discusses the modalities of use of PROs in HF, summarizes the most largely adopted PROs in HF care, and provides an overview on the application of PROs in trials and the potential for their transition to clinical practice. By discussing the advantages and the disadvantages of their use, the reasons limiting their application in daily clinical routine, and the strategies that may promote their implementation, this review aims to foster the systematic integration of the patient's standpoint in HF care. Abstract : Pros and cons of patient‐reported outcome (PRO) use in clinical practice. EHR, electronic health record; PRS, patient‐reported symptoms; QoL, quality of life.